Uncovering strategies of hidden intention in multi-stakeholder initiatives: The case of pasture-raised milk - Sarah Gauly; Sarah Kühl; Achim Spiller (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2017)
Sustainability management often requires voluntary initiatives beyond legal regulations. Hereby, multi-stakeholder initiatives (MSIs) gain importance. Despite the actual high occurrence of these initiatives, little information concerning the stakeholders' negotiation behaviour in MSIs exists. In this paper, we analyse a MSI related to the implementation of a sustainability-oriented standard for pasture-raised milk in Germany using participatory research. The results indicate that from an economic point of view not all stakeholders behave in a predictable way. Contrary to the assumption, one dairy involved in the MSI following a cost leadership strategy, pled for a high standard, as did the non-governmental organisations (NGOs) involved. Because this dairy was unable to fulfil this high standard, this behaviour can be interpreted as a 'prevention strategy'. It can be concluded that the classical assumption of stakeholder behaviour - such as tit-for-tat negotiations between the economic side and NGOs - must be reviewed, revealing strategies of hidden intention.
Keywords: 330; multi-stakeholder initiative; stakeholder negotiation strategies; prevention strategy; hidden intention; pasture-raised milk; sustainability